Haemophilus paraphrophilus brain abscess in a 9-year-old boy: Case report and literature review - Hind ZRIKEM; Loubna AIT SAID; Kawtar ZAHLANE (International Journal of Applied Biology, 2020)
Human diseases due to A. paraphrophilus aren’t usual. The following case report describes the first isolated case of A. paraphrophilus brain abscess in our laboratory. A 9-year-old boy presented to pediatric emergencies for frontal headache, vomiting, blurred vision and left hemiparesis. Radiological diagnosis consists with a frontal abscess. Gram staining of purulent samples showed abundant neutrophils with gram negative bacilli. Culture was made on blood agar, chocolate agar, Chapman’s agar and incubated in 5% CO2 at 37°C for 24 hours. Positive culture was detected only on chocolate agar. It was monomicrobial with small yellowish non-hemolytic colonies. Gram stain of colonies showed pleomorphic gram-negative coccobacilli. The strain required V factor for growth. The isolated strain was sensitive to all antibiotics tested.  The interest of this case is that it shows the emergence of A. paraphrophilus as a causative agent of brain abscesses on pediatric population without associated congenital heart disease. It may also help identifying risk factors of these infections and how to prevent them.